(untitled) (Journal of actual problems of jurisprudence, 2016)
It is very important to understand correctly the legal nature of terms which are used in a criminal sudoprizvodstvo. This article is devoted to formation of some concept and terms in criminal legal procee- dings. Besides, the analysis of different views of scientists on this problem is given.